Environmental characterization and cartographic modeling of wild plant habitats at the northern coastal zone of Egypt - El-Zeiny, Ahmed M.; Nour-Eldin, Hoda; Mohamed, E. S. Said; Rebouh, Nazih Y.; El-Amier, Yasser A. (Frontiers in Environmental Science, 2023)
Assessing natural vegetation through conventional methods faces considerable constraints, such as limited geographical scope, reduced precision, a lack of historical data, and high expenses and time demands. The study aims to use environmental and spectral data to identify and map natural vegetation and plant species along the Mediterranean coast of Egypt. This involves employing spatial analyses and cartographic modeling techniques, marking an initial effort in this mapping Arthrocnemum macrostachyum which that the middle coastal region is most suitable for its growth. It's recommended to integrate remotely sensed data with spatial analyses for the environmental analyses of natural plants. Present findings support researchers and scientists interested in environmental, botanic, and medical studies.